ANALISIS HASIL VALIDITAS INSTRUMEN ASESMEN PEMBELAJARAN BERORIENTASI LITERASI SAINS BERBANTUAN MEMORY FLASHCARD PADA SISWA KELAS III SEKOLAH DASAR - Synthia; Dwi Cahaya Nurani; Suratmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the validity of a science literacy-oriented learning assessment instrument assisted by memory flashcards on the Life Cycle of Living Things material for third-grade elementary school students. The research method uses a quantitative descriptive approach with data collection techniques thru a validation questionnaire assessed by assessment experts, content experts, and two practitioner experts. The data was analyzed quantitatively and descriptively using a Likert scale and the feasibility percentage was calculated. The validation results show that this assessment instrument is considered highly valid, with an average percentage of 92% from assessment experts, 95% from content experts, and 96.2% from practitioner experts. Revisions based on validator suggestions focused on balancing the material (humans, animals, plants) and aligning the questions with the three aspects of scientific literacy (content, process, context). The conclusion of this research is that the learning assessment instrument developed with the aid of memory flashcards has met high validity criteria, is suitable for use, and has the potential to become an interactive and contextual assessment medium to support the science literacy of third-grade students according to the characteristics of Generation Alpha.